MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 1A DI MIN 7 SELUMA MENGUNAKAN KARTU KATA HURUF - Eti Marda Yanti; Reni Kusmiarti; Adi Asmara (JURNAL ILMU PENDIDIKAN, 2025)
This study aims to improve the early reading ability of Grade 1A students at MIN 7 Seluma through the use of word/letter card media. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 25 students of Grade 1A in the current academic year. Data were collected through observation sheets, learning outcome tests, and documentation. The pre-action test results showed that only 8 students (32%) achieved the Minimum Mastery Criteria (score ≥70), while 17 students (68%) had not yet reached the standard. After the implementation of word/letter card media in Cycle I, the number of students who achieved mastery increased to 15 students (60%). However, since the success indicator (≥75% of students achieving mastery) had not been met, the research proceeded to Cycle II with an improved strategy by incorporating small group games. The results of Cycle II revealed a significant improvement, with 21 students (84%) reaching the Minimum Mastery Criteria, while 4 students (16%) remained below the standard. These findings indicate that the use of word/letter card media is effective in improving students’ early reading skills, enhancing active participation, increasing motivation, and creating a more enjoyable learning atmosphere